2018
DOI: 10.21608/ejprs.2018.78362
|View full text |Cite
|
Sign up to set email alerts
|

Plate and Screw Versus Intramedullary K Wire for Fixation of Unstable Metacarpal and Phalangeal Fractures

Abstract: Background: Unstable metacarpal and phalangeal fractures represent more than one third fractures of the hand. The severe the trauma, the more grave the fracture that herald perfect management is needed.Objective: Assessment of the clinical and radiological outcomes of metacarpal and proximal phalangeal fractures in patients who underwent open anatomic reduction and fixation with plate and screws or by intramedullary K wire fixation.Patients and Methods: Twenty five patients with unstable metacarpal and phalang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Ahmad I et al [38] reported the results of 22 patients with an average age of 9.5 years having unstable radius ulna forearm fractures. They observed excellent outcome in 18(82%) patients, good in 2(9%) and fair in 2 (9%) patients.…”
mentioning
confidence: 99%
“…Ahmad I et al [38] reported the results of 22 patients with an average age of 9.5 years having unstable radius ulna forearm fractures. They observed excellent outcome in 18(82%) patients, good in 2(9%) and fair in 2 (9%) patients.…”
mentioning
confidence: 99%
“…[9][10][11] Certain disadvantages of open reduction include skin scaring, injury to tendons, second surgery to remove the plate, expensive and demands appropriate skills. [12][13][14] Abdel Wahed et al compared different designs of locking plates, using fixed angle volar locking plates in 65 patients and variable angle volar locking plates in 48 patients with unstable distal radius fractures. The study concluded that the variable angle system is slightly better in terms of function and radiographic outcomes.…”
Section: Discussionmentioning
confidence: 99%